2019
DOI: 10.3802/jgo.2019.30.e96
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the precursors of high grade serous ovarian cancer and patient characteristics: decreased incidence of the p53 signature in pregnant women

Abstract: ObjectiveTo investigate the relationship between the precursors of high grade serous ovarian cancer (HGSOC) and the characteristics of patients with a low HGSOC risk in terms of the effects of pregnancy.MethodsWe prospectively examined consecutive cases in which the bilateral fallopian tubes were removed during benign gynecological or obstetric surgery and assessed the relationship between the patient characteristics, including parity and pregnancy, and the incidence of HGSOC precursors. All the fallopian tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Ovarian cancer is asymptomatic in its early stages, and the rapid growth of ovarian cancer makes its diagnosis and treatment challenging ( 4 , 5 ). Serous ovarian cancer (SOC) is the main type of ovarian cancer, which progresses quickly, lacks effective treatment and is prone to bladder metastasis ( 6 ). At present, surgery supplemented by chemotherapy remains the main treatment option for advanced stages of SOC, and treatment outcomes are unsatisfactory ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is asymptomatic in its early stages, and the rapid growth of ovarian cancer makes its diagnosis and treatment challenging ( 4 , 5 ). Serous ovarian cancer (SOC) is the main type of ovarian cancer, which progresses quickly, lacks effective treatment and is prone to bladder metastasis ( 6 ). At present, surgery supplemented by chemotherapy remains the main treatment option for advanced stages of SOC, and treatment outcomes are unsatisfactory ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 138 women who underwent BTL during S/C were included in this study. The mean age was 34.62 , the mean gravity was 4.89 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and the mean parity was 3.46 (1-10). In the extended period, which includes the study period (between 15 August 2020 and 31 December 2021), there were 4568 S/Cs, 643 BTLs, and 2 re-anastomoses in our institution.…”
Section: Resultsmentioning
confidence: 99%
“…Most of them are bilateral. Low-grade OSC is uncommon (<5% of all ovarian cancers) [10,12]. High and low-grade OSCs are said to have different carcinogenesis origins [13].…”
Section: Introductionmentioning
confidence: 99%
“…9 Our group previously reported that the incidence of the p53 signature in fallopian tubes was significantly lower in pregnant and parous women. 10 Another report suggested that progesterone from follicular fluid during ovulation induces necroptosis in p53 mutated tubal epithelial cells and prevents carcinogenesis. 11 Progesterone may prevent early-phase serous carcinogenesis and suppress ovarian cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%